Method for preparing transparent conductive oxide film by using low-indium-content target material
By using low-indium content targets and magnetron sputtering method to prepare transparent conductive oxide films, the problem of strong dependence on rare metal indium in the prior art is solved, and the film is low resistivity, high transmittance and high temperature are achieved Stability reduces the manufacturing cost of HJT batteries.
Patent Information
- Application Number
- CN202411622636.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the preparation of transparent conductive oxide thin films, it is difficult to effectively reduce the dependence on rare metal indium, resulting in high costs and large resource consumption. Especially in the development of HJT solar cell technology, the demand for indium has increased sharply. It is difficult to meet future production expansion needs with technology.
Using a low indium content target, by mixing 2%-25% nano-scale indium oxide powder with zinc oxide powder in mass percentage, adding an appropriate amount of deionized water, adhesive and surface modifier, and grinding, ball milling and Spray granulation treatment is used to form a slurry with high solid content, and a transparent conductive oxide film is prepared by magnetron sputtering.
It realizes efficient preparation of low indium targets, has low resistivity, high transmittance, and high temperature stability, effectively reducing the TCO manufacturing cost of HJT batteries and reducing dependence on indium.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of methods for preparing zinc indium oxide thin films, and in particular to a method for preparing a transparent conductive oxide thin film by using a target material with a low indium content. Background Art
[0002] Transparent conductive oxide films are widely used in solar cells, semiconductor displays, touch screens, smart windows, stealth fighters, electromagnetic shielding, and automotive defogger glass. Among them, with the rapid development of heterojunction solar cell technology and display technologies such as semiconductor TFT, OLED, and mini-LED, the global demand for transparent conductive oxide film materials has increased dramatically. Common transparent conductive oxide material systems mainly include indium oxide-based, tin oxide-based, and zinc oxide-based. They are usually prepared as targets and prepared into films and corresponding electronic components using magnetron sputtering technology. Indium oxide-based transparent conductive oxide films have become the most widely used transparent conductive oxide film materials due to their outstanding characteristics such as high visible light transmittance, low sheet resistance, friction resistance, and corrosion resistance. With the rapid development of heterojunction solar cell technology, the demand for indium oxide-based transparent conductive film materials in the photovoltaic industry has increased dramatically.
[0003] Indium tin oxide thin films are usually made of indium tin oxide targets, which are coated by magnetron sputtering to form thin films. The raw materials of indium tin oxide targets are metal indium and metal tin. The content of metal indium in the earth's crust is extremely low (0.056×10 -6), scattered distribution, its rich mines have not been discovered so far. 90% of the world's indium production comes from by-products of lead and zinc smelters, so metallic indium is listed as a rare metal element and a scarce resource. It has been included in the "List of Critical Minerals" by many countries such as China, the United States, Japan, Canada and Australia, and is also listed as a strategic metal. The estimated global indium resources are only 76,000 tons, and China's indium resources are 21,600 tons, of which only 50% can be mined. The industry uses the method of purifying waste zinc and waste tin to produce metallic indium, and the recovery rate is only 50-60%. In this way, the world can only get 19,000-23,000 tons of indium. In 2023, China's refined indium production will be only 1,400 tons, of which Shaoguan will produce 700 tons, accounting for 50%, of which the demand for refined indium for flat displays is as high as 1,200 tons / year. With the rapid development of HJT solar cell technology, the effective production capacity of HJT batteries will reach 42.3GW in the first half of 2024, and the demand for indium will reach 170 tons. According to the HJT Industry Development White Paper (2024) released by SOLARZOOM, the conservative annual shipment of HJT solar cell components will reach 619GW in 2028, and the corresponding indium consumption will reach more than 2,500 tons / year. The demand for indium in the photovoltaic field has increased dramatically. With the existing technology, the reserves and output of indium will not be able to meet the expansion needs of HJT cells in the future. Therefore, it is of great significance to develop targets with low indium content and reduce the consumption of indium in HJT cells.
[0004] Patent No. CN 118084480 A proposes a method for preparing a high-density, low-indium-content ITO target material, which uses indium oxide and tin oxide micro-nano powders in proportion to the indium content, and adds a sintering agent, antimony trioxide, to prepare an ITO target material with an indium content of 40.5-42%, a relative density of ≥99.5%, and a resistivity of ≤1×10 -3 Ω·cm. Patent No. CN 116496081 A proposes an indium tin oxygen ternary compound target material and its preparation method and application. In2O3 and SnO2 powders are mixed and pre-sintered to obtain indium tin oxygen ternary compound powder, and then prepared into a target material. The mass percentage of In element in the target material is 43.5-55.7%, the relative density of the target material is ≥98%, and the resistivity is ≤5.0E-3Ω·cm. However, for magnetron sputtering technology, there is no obvious positive correlation between the resistivity of the film and the resistivity of the corresponding target material. In addition to the target material itself, the resistivity of the film is also related to the sputtering coating atmosphere and content, sputtering pressure, sputtering power, background vacuum and other sputtering parameters and the magnetic field strength inside the machine. In addition, for heterojunction solar cells, one of the core processes is screen printing low-temperature silver paste. The printed paste and TCO film will be cured at 200°C in a low-temperature dryer. Therefore, the TCO film of the heterojunction battery must also have special requirements for high-temperature stability. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a transparent conductive oxide film using a low indium content target material, which can effectively reduce the TCO manufacturing cost of HJT cells and reduce the dependence of HJT cells on indium.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a transparent conductive oxide film using a low indium content target material, comprising the following steps:
[0007] The low indium target material preparation step comprises: mixing 2% to 25% of nano-scale indium oxide powder and the remaining zinc oxide powder uniformly according to the mass percentage content to obtain a mixed powder.
[0008] Deionized water with a conductivity of less than 0.5 μs / cm, 0.5-0.9% of polyvinyl alcohol as a binder, and 0.5-1.3% of polyvinyl pyrrolidone as a surface modifier are added to the mixed powder according to mass percentage, and the mixture is evenly stirred and then ground and dispersed for 1-3 hours to obtain a first slurry, wherein the solid content of the first slurry is 45-70%.
[0009] 0.2-1% of defoamer n-octanol, 0.2-1% of sintering aid Bi2O3 and 0.2-1% of Sb2O3 are added to the first slurry by mass percentage, and then ball milling is performed for 1-3 hours. The powder particle size of the powder in the first slurry is reduced by ball milling, and the powder particle size D90 of the first slurry is less than 500nm, so as to obtain a second slurry with a solid content of 43-66%.
[0010] The second slurry is used for spray granulation treatment, the air inlet temperature is set to 198-212° C., and the air outlet temperature is set to 85-95° C. to obtain dry powder, and the dry powder is subjected to cyclone separation so that the particle size D90 of the dry powder is less than 300 nm;
[0011] Use dry powder to perform cold isostatic pressing in sequence, set the pressure to 20±5Mpa, press for 30±5min, then set the pressure to 280-320MPa, press for 1±0.5h, and obtain a green body with a relative density of ≥58%.
[0012] The green body is placed in a sintering furnace for sintering, the sintering temperature is set to 600±50°C, the temperature gradient is 0.2-0.5°C / min, and the temperature is kept for 2±0.5h, and then the temperature is set to 1360-1450°C, the temperature gradient is 0.2-0.5°C, and the temperature is kept for more than 180 hours, and then cooled according to the same temperature gradient, and a low indium target is obtained after cooling to room temperature;
[0013] The transparent conductive oxide film preparation step uses a low indium target material and is prepared by magnetron sputtering to obtain a transparent conductive oxide film by sputtering coating.
[0014] The sputtering background vacuum is greater than 2×10 -3 Pa, sputtering pressure is 0.3-1Pa, and planar target sputtering power density is 1-5W / cm 2 If it is a rotating target, the power density is 2-10kw / m, and the O2 / Ar flow rate is 0%-10%.
[0015] A further technical solution is that the low indium target material preparation step is:
[0016] The zinc oxide powder has a particle size D90 < 5um and a specific surface area of 5-25m 2 / g,
[0017] The indium oxide powder has a particle size D90 < 5um and a specific surface area of 5-25m 2 / g.
[0018] A further technical solution is that the low indium target material preparation step is:
[0019] Deionized water with a conductivity of less than 0.5 μs / cm, 0.7% of a binder polyvinyl alcohol and 0.9% of a surface modifier polyvinyl pyrrolidone were added to the mixed powder in percentage by mass, and the mixture was uniformly stirred and then ground and dispersed for 2 hours to obtain the first slurry, wherein the solid content of the first slurry was 66%.
[0020] 0.7% of defoaming agent n-octanol, 0.41% of sintering aid Bi2O3 and 0.6% of Sb2O3 were added to the first slurry by mass percentage, and then ball milling was carried out for 2 hours. The powder particle size of the powder in the first slurry was reduced by ball milling, and the powder particle size D90 of the first slurry was reduced to 450nm, thereby obtaining the second slurry with a solid content of 54%.
[0021] A further technical solution is that the low indium target material preparation step is:
[0022] The abrasive used in the ball milling process includes zirconium balls with a diameter of 1-10 mm, the rotation speed of the ball mill is 180±20 r / min, and the ball milling time is 2±0.5 hours.
[0023] A further technical solution is that in the step of preparing the low indium target material, the second slurry is used for spray granulation treatment, the inlet temperature of the spray granulator is set to 198-212°C, and the outlet temperature is set to 85°C-95°C, dry powder is obtained by spray granulation treatment, and the dry powder is subjected to cyclone separation so that the particle size D90 of the dry powder is less than 300nm.
[0024] The dry powder is sieved with a sieve of 120-180 meshes, and after sieving, the dry powder is loaded into a mold and subjected to ultrasonic vibration for 10±2 minutes to reduce the powder surface energy of the dry powder, and then the dry powder is sequentially subjected to compression molding and cold isostatic pressing to obtain the green body.
[0025] A further technical solution is that the low indium target material preparation step is:
[0026] The green body is placed in the sintering furnace for sintering, and the temperature rise gradient of the sintering furnace is set to 0.5°C / min. The temperature of the sintering furnace is first increased to 600°C, and then the temperature of the sintering furnace is increased to 1360-1450°C at a temperature rise gradient of 0.5°C / min after being kept warm for 2 hours. After being kept warm for 180-200 hours, the temperature of the sintering furnace is cooled to 150-100°C at a temperature drop gradient of 0.5°C / min, and finally naturally cooled to room temperature to obtain the low indium target.
[0027] In a further technical solution, the transparent conductive oxide film preparation step is:
[0028] The low-indium target is bound to a copper backplane, and then loaded into a magnetron sputtering coating machine for magnetron sputtering coating. The magnetron sputtering coating machine is controlled to be evacuated to below 1.5E-3Pa, the sputtering pressure is set to 0.3-0.6Pa, the cavity temperature is 20-35°C, the sputtering time is 500-600s, the film thickness is 100nm±10nm, the sputtering power is set to 500W-2000W, the argon flow rate is set to 50-200sccm, and the oxygen flow rate is set to 0-20sccm to obtain the transparent conductive oxide film.
[0029] Compared with the prior art, the advantages of the present invention are as follows: the present invention adopts indium oxide doped with zinc oxide to prepare a low indium content target material, which has the advantages of low cost, low target material resistivity, and high relative density. The film obtained by the sputtering coating process has low resistivity, high transmittance, and high temperature stability, which effectively reduces the TCO manufacturing cost of the HJT battery and reduces the dependence of the HJT battery on indium. DETAILED DESCRIPTION
[0030] Example 1
[0031] A method for preparing a transparent conductive oxide film using a low indium content target material comprises the following steps:
[0032] The low indium target material preparation step (target material preparation step) is to mix 2% of nano-grade zinc oxide powder and the remaining indium oxide powder according to the mass percentage content to obtain a mixed powder. The powder particle size D90 of the zinc oxide powder and the indium oxide powder used is 5um, and the specific surface area is 5-25m 2 / g.
[0033] Deionized water with a conductivity of less than 0.5 μs / cm, 0.7% of adhesive polyvinyl alcohol and 0.9% of surface modifier polyvinyl pyrrolidone were added to the mixed powder by mass percentage, stirred evenly, and then ground and dispersed for 2 hours to obtain a first slurry with a solid content of 66%.
[0034] 0.7% of defoaming agent n-octanol, 0.41% of sintering aid Bi2O3 and 0.6% of Sb2O3 were added to the first slurry by mass percentage, and then ball milling was performed for 2 hours. The powder particle size of the powder in the first slurry was reduced by ball milling to make the powder particle size D90 450nm, and a second slurry with a solid content of 54% was obtained.
[0035] The second slurry is used for spray granulation treatment, the inlet temperature of the spray granulator is set to 205° C., and the outlet temperature is set to 93° C., and dry powder is obtained by spray granulation treatment, and the dry powder is sieved with a sieve with a mesh number of 180, and after sieving, the dry powder is loaded into a mold, and ultrasonic vibration is performed for 10 minutes to reduce the powder surface energy of the dry powder, and then the dry powder is used to perform compression molding treatment and cold isostatic pressing treatment in sequence, and the pressure of the cold isostatic pressing treatment is set to 310 MPa and the time is set to 2 hours to obtain the green body, and the relative density of the green body is ≥58%;
[0036] The green body is placed in the sintering furnace for sintering, and the temperature rise gradient of the sintering furnace is set to 0.3°C / min. The temperature of the sintering furnace is first increased to 600°C, and then the temperature is increased to 1430°C at a temperature rise gradient of 0.5°C / min after being kept warm for 3 hours. After being kept warm for 180 hours, the temperature of the sintering furnace is cooled to 100°C at a temperature drop gradient of 0.3°C / min, and finally naturally cooled to room temperature to obtain a low indium target.
[0037] The low-indium target is bound to a copper backplane, and then loaded into a magnetron sputtering coating machine for magnetron sputtering coating. The magnetron sputtering coating machine is controlled to be evacuated to below 1.5E-3Pa, the sputtering pressure is set to 0.5Pa, the chamber temperature is 25°C, the sputtering time is 500-600s, the film thickness is 100nm±10nm, the sputtering power is set to 1200W, the argon flow rate is set to 100sccm, and the oxygen flow rate is set to 0-1sccm to obtain the transparent conductive oxide film.
[0038] The transparent conductive oxide film was annealed on a hot plate at different temperatures in an air environment for 30 minutes. The average visible light transmittance and resistivity performance parameters of the film in the 380-760nm band were tested before and after annealing, as shown in Table 1.
[0039] As can be seen from Table 1, the transmittance of the film of Example 1 is significantly improved compared with that of Comparative Example 1, and the transmittance is increased from 83% to 85.3%. The resistivity of the film after annealing is much lower than that of the film of Comparative Example 1. This is because after the addition of 2% indium oxide, the indium in the film combines with oxygen, resulting in a decrease in the concentration of oxygen vacancies inside the film, thereby increasing the transmittance of the film. However, when an excessive amount of indium oxide is doped, a higher concentration of indium will lead to the segregation of indium-rich phases in the film crystals, reduce the uniformity of element distribution of the film, generate a large number of grain boundary defects inside the film, form grain boundary scattering, hinder the migration of electrons, and increase the resistivity of the film.
[0040] Example 2
[0041] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of Example 2 is the same as that of Example 1, except that 5% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed uniformly according to the mass percentage content, and all other contents are the same.
[0042] Example 3
[0043] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of Example 3 is the same as that of Example 1, except that 8% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed uniformly according to the mass percentage content, and all other contents are the same.
[0044] It can be seen from Example 3 that after the transparent conductive oxide film prepared was annealed in air at 200°C, the resistivity of the transparent conductive oxide film only increased slightly, from 3.24E-3Ω·cm to 4.86E-3Ω·cm, indicating that the low-indium film prepared in this example has good high-temperature stability.
[0045] Example 4
[0046] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of Example 4 is the same as that of Example 1, except that 13% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed evenly according to the mass percentage content, and all other contents are the same.
[0047] It can be seen from Example 4 that the transparent conductive oxide film prepared therein has good transmittance before and after annealing, and the average transmittance in the 380-760 nm band is as high as 84%.
[0048] Example 5
[0049] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of Example 5 is the same as that of Example 1, except that 18% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed evenly according to the mass percentage content, and all other contents are the same.
[0050] It can be seen from Example 5 that after the prepared transparent conductive oxide film is annealed in air at 200° C., the resistivity of the transparent conductive oxide film increases only slightly, from 2.98Ω·cm to 5.83Ω·cm, indicating that the transparent conductive oxide film has good high temperature stability.
[0051] Example 6
[0052] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of Example 6 is the same as that of Example 1, except that 25% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed evenly according to the mass percentage content, and all other contents are the same.
[0053] Comparative Example 1
[0054] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of comparative example 1 is the same as that of embodiment 1, except that 45% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed uniformly according to the mass percentage content, and all other contents are the same.
[0055] It can be seen from Comparative Example 1 that the resistivity of the target material in Comparative Example 1 is the lowest, and the resistivity of the transparent conductive oxide film prepared therefrom is also the lowest before annealing. However, after annealing in air at 200°C for 30 minutes, the film resistivity of the transparent conductive oxide film increases significantly, indicating that the high-temperature stability of the transparent conductive oxide film at 200°C is relatively poor. This is because before annealing, the indium atoms on the film lattice replace the zinc atoms, providing more free electrons, thereby increasing the carrier concentration of the film, improving the conductivity of the film, and making the resistivity of the film smaller. However, after the film is annealed at a high temperature of 200°C, indium precipitates from the zinc oxide grain boundary, locally forming an amorphous In-Zn-O phase, and the carrier concentration decreases, resulting in a significant increase in the resistivity of the film.
[0056] Comparative Example 2
[0057] A method for preparing a transparent conductive oxide film using a low indium content target material. The preparation process of comparative example 2 is the same as that of embodiment 1, except that 35% of nano-scale indium oxide powder and the remainder of zinc oxide powder are stirred and mixed uniformly according to the mass percentage content, and all other contents are the same.
[0058] The samples prepared in Examples 1-7 and Comparative Example 1 were tested, as shown in Table 1 for details.
[0059]
[0060] Table 1 Test parameter comparison table.
Claims
1. A method for preparing a transparent conductive oxide film using a low indium content target, characterized in that: The following steps are included: The low indium target material preparation step comprises: mixing 2% to 25% of nano-scale indium oxide powder and the remaining zinc oxide powder uniformly according to the mass percentage content to obtain a mixed powder. Deionized water with a conductivity of less than 0.5 μs / cm, 0.5-0.9% of polyvinyl alcohol as a binder, and 0.5-1.3% of polyvinyl pyrrolidone as a surface modifier are added to the mixed powder according to mass percentage, and the mixture is evenly stirred and then ground and dispersed for 1-3 hours to obtain a first slurry, wherein the solid content of the first slurry is 45-70%. 0.2-1% of defoamer n-octanol, 0.2-1% of sintering aid Bi2O3 and 0.2-1% of Sb2O3 are added to the first slurry by mass percentage, and then ball milling is performed for 1-3 hours. The powder particle size of the powder in the first slurry is reduced by ball milling, and the powder particle size D90 of the first slurry is less than 500nm, so as to obtain a second slurry with a solid content of 43-66%. The second slurry is used for spray granulation treatment, the air inlet temperature is set to 198-212° C., and the air outlet temperature is set to 85-95° C. to obtain dry powder, and the dry powder is subjected to cyclone separation so that the particle size D90 of the dry powder is less than 300 nm; Use dry powder to perform cold isostatic pressing in sequence, set the pressure to 20±5Mpa, press for 30±5min, then set the pressure to 280-320MPa, press for 1±0.5h, and obtain a green body with a relative density of ≥58%. The green body is placed in a sintering furnace for sintering, the sintering temperature is set to 600±50°C, the temperature gradient is 0.2-0.5°C / min, and the temperature is kept for 2±0.5h, and then the temperature is set to 1360-1450°C, the temperature gradient is 0.2-0.5°C, and the temperature is kept for more than 180 hours, and then cooled according to the same temperature gradient, and a low indium target is obtained after cooling to room temperature; The transparent conductive oxide film preparation step uses a low indium target material and is prepared by magnetron sputtering to obtain a transparent conductive oxide film by sputtering coating. The sputtering background vacuum is greater than 2×10 -3 Pa, sputtering pressure is 0.3-1Pa, and planar target sputtering power density is 1-5W / cm 2 If it is a rotating target, the power density is 2-10kw / m, and the O2 / Ar flow rate is 0%-10%.
2. The method for preparing a transparent conductive oxide film using a low indium content target according to claim 1, characterized in that: The low indium target material preparation step, The zinc oxide powder has a particle size D90 < 5um and a specific surface area of 5-25m 2 / g, The indium oxide powder has a particle size D90 < 5um and a specific surface area of 5-25m 2 / g.
3. The method for preparing a transparent conductive oxide film using a low indium content target according to claim 1, characterized in that: The low indium target material preparation step, Adding deionized water with a conductivity of less than 0.5 μs / cm, 0.7% of a binder polyvinyl alcohol, and 0.9% of a surface modifier polyvinyl pyrrolidone to the mixed powder by mass percentage, stirring evenly, and then grinding and dispersing for 2 hours to obtain the first slurry, wherein the solid content of the first slurry is 66%; 0.7% of defoaming agent n-octanol, 0.41% of sintering aid Bi2O3 and 0.6% of Sb2O3 were added to the first slurry by mass percentage, and then ball milling was carried out for 2 hours. The powder particle size of the powder in the first slurry was reduced by ball milling, and the powder particle size D90 of the first slurry was reduced to 450nm, thereby obtaining the second slurry with a solid content of 54%.
4. The method for preparing a transparent conductive oxide film using a low indium content target according to claim 1, characterized in that: The low indium target material preparation step, The abrasive used in the ball milling process includes zirconium balls with a diameter of 1-10 mm, the rotation speed of the ball mill is 180±20 r / min, and the ball milling time is 2±0.5 hours.
5. The method for preparing a transparent conductive oxide film using a target material with low indium content according to claim 1, characterized in that: The low indium target material preparation step, The second slurry is used for spray granulation treatment, the inlet temperature of the spray granulator is set to 198-212° C., and the outlet temperature is set to 85° C.-95° C., and dry powder is obtained by spray granulation treatment, The dry powder is sieved with a sieve of 120-180 meshes, and after sieving, the dry powder is loaded into a mold and subjected to ultrasonic vibration for 10±2 minutes to reduce the powder surface energy of the dry powder, and then the dry powder is sequentially subjected to compression molding and cold isostatic pressing to obtain the green body.
6. The method for preparing a transparent conductive oxide film using a low indium content target according to claim 1, characterized in that: The low indium target material preparation step, The green body is placed in the sintering furnace for sintering, and the temperature rise gradient of the sintering furnace is set to 0.5°C / min. The temperature of the sintering furnace is first increased to 600°C, and then the temperature of the sintering furnace is increased to 1360-1450°C at a temperature rise gradient of 0.5°C / min after being kept warm for 2 hours. After being kept warm for 180-200 hours, the temperature of the sintering furnace is cooled to 150-100°C at a temperature drop gradient of 0.5°C / min, and finally naturally cooled to room temperature to obtain the low indium target.
7. A method for preparing a transparent conductive oxide film using a low indium content target according to any one of claims 1 to 6, characterized in that: The transparent conductive oxide film preparation step, The low-indium target material is bound to a copper back plate, and then loaded into a magnetron sputtering coating machine for magnetron sputtering coating. The magnetron sputtering coating machine is controlled to be evacuated to 1.5×10 -3 Pa, the sputtering pressure is set to 0.3-0.6Pa, the chamber temperature is 20-35°C, the sputtering time is 500-600s, the film thickness is 100nm±10nm, the sputtering power is set to 500W-2000W, the argon flow rate is set to 50-200sccm, and the oxygen flow rate is set to 0-20sccm to obtain the transparent conductive oxide film.
Citation Information
Patent Citations
Indium tin oxide ternary compound target material and preparation method and application thereof
CN116496081A
Zinc oxide analog amorphous film sputtering target and its manufacture method
CN101333644A
Indium-doped zinc oxide target material and preparation method of transparent conducting film
CN102191465A
In2o3-zno sputtering target
US20140102892A1